PENGARUH VIDEO ANIMASI DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI - Wahyudi, Eko; Farihah, Umi; Umam, Khotibul (STIT AL MULTAZAM, 2023)
The limited time teachers have in providing teaching materials is an obstacle to improving the quality of learning. PAI materials require a high level of understanding. However, students still have difficulty in understanding PAI materials. The purpose of this study was conducted to determine whether the Animated Video media has an effect on student learning outcomes, whether learning motivation has an effect on student learning outcomes and whether there is an interaction effect of using Animated Video and learning motivation on student learning outcomes in PAI subjects. The approach and type of research used quasi-experimental quantitative research. The subject of this research was fifth grade students of SDI Darussalam Al hafidziyah Jember. Samples were taken using Purposive Sampling technique. Data on learning motivation was collected by questionnaire and data on student learning outcomes was collected by test method. The analysis was conducted using ANOVA. It can be concluded that there is an influence of animated video media and learning motivation on student learning outcomes in PAI Class V subjects at SDI Darussalam Al Hafidziyah Jember, because animated videos can be a very effective tool in education because they can help visualise difficult concepts, make learning more interesting, and help students understand the material better. This can be the basis for continuing to integrate multimedia technology in the learning process to improve student understanding and learning outcomes.